The Status Quo of Hibah in Property Dispute Settlement in Malaysian Courts (Kanun: Jurnal Undang-undang Malaysia, 2022)
In achieving the well-being of the ummah, wealth management through various property planning instruments is important. This article examines the status quo of hibah in Malaysia, including practices, sources of authority, jurisdiction, and court decisions in hibah-related cases. This legal study is qualitative in nature and employs a descriptive analysis, which involves collecting data through various books, journals, and documents of legal texts such as Parliamentary acts, state enactments, and Shari’ah resolutions. Together with six themes of analysis, a concept is formulated based on the references and analysis of decided court cases. It is found that Malaysia’s hibah practices are separated into two categories, subject to different sets of laws and courts: non-commercial grant contracts and commercial grant contracts. Although hibah is enumerated under List 2 of the Ninth Schedule of the Federal Constitution, conflicts of jurisdiction may arise through the development of contemporary concepts of hibah and contract implementation. The findings show that all cases related to non-commercial hibah contracts are subject to the Syariah Court’s jurisdiction. In contrast, commercial hibah contract cases will be decided in the Civil Courts. As a result of the lack of standard statutory legislation at the Syariah Court, a large lacuna exists and various approaches are adopted in determining the validity of hibah. It is recommended that a specific, holistic and comprehensive hibah legislation be enacted to standardize and coordinate hibah in Malaysia.Keywords: Dispute settlement, hibah, comercia, court, property, jurisdictionFull text: PDF